Discussion of on the Frequency, Quality, and Informational Role of Mandatory Financial Reports - Dye, Ronald A. (Journal of Accounting Research, 1998)
Ronald A. Dye, Discussion of on the Frequency, Quality, and Informational Role of Mandatory Financial Reports, Journal of Accounting Research, Vol. 36, Studies on Enhancing the Financial Reporting Model (1998), pp. 149-160